(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
Writing was introduced in ancient Italy through the contact between Greek sailors and Etruscan aristocracies in the Orientalizing period. As part of the ritual relationships among peers, writing spread quickly to the nearby peoples and in the course of the sixth century BCE became a marker of ethnic identity, thus creating a mosaic of diverse graphic traditions, from time to time derived directy from Greek writing or through the Etruscan or Latin mediation. The chapter includes an introductory part on the historical process of transmission and adaptation of writing and a survey of the epigraphic domains of ancient Italy: Etruscan, Faliscan, Latin, Celtic, Venetic, Rhetian, Camunian, Paleo-Italic, Paleo-Sabellic, Ausonian, Oscan and Umbrian. In conclusion, some suggestions for future research are briefly presented.